2019
DOI: 10.1111/aec.12708
|View full text |Cite
|
Sign up to set email alerts
|

Grass greenness and grass height promote the resource partitioning among reintroduced Burchell's zebra and blue wildebeest in southern Mozambique

Abstract: Differences in the selection of habitat and specific dietary items support resource partitioning and coexistence of sympatric African grazing herbivores, such as zebra and wildebeest. In Maputo Special Reserve (MSR), southern Mozambique, these two species were extirpated during the civil war (1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992); since 2010, they have been reintroduced into the Reserve. Identifying the resource selection by reintroduced species and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…This would reflect the dietary importance of grass, which provides more than 90% of the zebra diet (Grubb, 1981) and 95% of the wildebeest diet (Duncan, Foose, Gordon, Gakahu, & Lloyd, 1990), with the contribution increasing where tree cover is low (Riginos & Grace, 2008). We found that, the odds of use of habitat by both herbivore species decreased with increases in wood cover (Table 5), and, the grass Aristida barbicollis, which contributed most to the diets of both herbivores, and was most preferred are indeed more available in the most preferred habitat (Mandlate, Arsenault, & Rodrigues, 2019).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This would reflect the dietary importance of grass, which provides more than 90% of the zebra diet (Grubb, 1981) and 95% of the wildebeest diet (Duncan, Foose, Gordon, Gakahu, & Lloyd, 1990), with the contribution increasing where tree cover is low (Riginos & Grace, 2008). We found that, the odds of use of habitat by both herbivore species decreased with increases in wood cover (Table 5), and, the grass Aristida barbicollis, which contributed most to the diets of both herbivores, and was most preferred are indeed more available in the most preferred habitat (Mandlate, Arsenault, & Rodrigues, 2019).…”
Section: Discussionmentioning
confidence: 62%
“…However, the principal predator of these two herbivores, the lion, is absent from the MSR, which may mean that predation would not be the factor determining the preference of these herbivores for open habitats at this site. We found that, the odds of use of habitat by both herbivore species decreased with increases in wood cover (Table 5), and, the grass Aristida barbicollis, which contributed most to the diets of both herbivores, and was most preferred are indeed more available in the most preferred habitat (Mandlate, Arsenault, & Rodrigues, 2019). This would reflect the dietary importance of grass, which provides more than 90% of the zebra diet (Grubb, 1981) and 95% of the wildebeest diet (Duncan, Foose, Gordon, Gakahu, & Lloyd, 1990), with the contribution increasing where tree cover is low (Riginos & Grace, 2008).…”
Section: Model For Predicting Habitat Usementioning
confidence: 88%
“…Therefore, our results suggest that in the trade-off between the potential competition for trophic resources and the benefits of increased predator detection, if the species involved do not completely overlap in their diets, the outcome of co-occurring within a landscape of fear (sensu Laundr e et al 2001) may result in a positive relationship (improved saferfeeling effect). In addition, foraging by livestock could keep the grass in an early stage of development, which may facilitate the access of lesser rhea to a better quality forage (Mandlate Jr et al 2019). Furthermore, ranchers tolerate lesser rhea within their fields since they do not perceive them as a species competing with livestock (own unpub.…”
Section: Discussionmentioning
confidence: 99%
“…Grass preference indices were assessed within each quadrat as 0 (no grass available), 1 (no grazing, i.e., none of the grass tufts showed bite marks), 2 (moderate grazing/very light grazing, i.e., partially eaten), 3 (heavy grazing) and 4 (intense grazing) [13]. Additionally, we visually assessed grass greenness as dry grass (a), pale green (b), green (c) and deep green (d) [20,33,34], (see supplementary information). However, ten termite mound areas and control sites in Miombo vegetation as well as some areas in grazing lawns edges were heavily affected by fire from July 2017 onwards and grass assessment was not possible in these sites.…”
Section: Data Collectionmentioning
confidence: 99%
“…Various mammalian grazers such as the wildebeest (Connochaetes taurinus) are attracted by short green grass of high nutrient content [18][19][20]. While the importance of grazing lawns for herbivores has been demonstrated [15,21,22] few experiments exist that quantified the extent to which these lawns attract grazers in nutrient poor areas [8].…”
Section: Introductionmentioning
confidence: 99%